Realising climate gains from smallholder chicken farming in Africa - Zewdie, Yihenew; Dessie, Tadelle (Technical Centre for Agricultural and Rural Cooperation, 2019)
There is hardly a document on African climate change issues that does not portray livestock husbandry in a negative light - responsible for emitting substantial quantities of greenhouse gases. While it is true that some livestock play a role in generating greenhouse gases, this is not the case across the entire sector. Chickens are among the few domestic animals that have a low environmental impact and carbon footprint, and research is moving forward to develop climate-smart poultry production for African smallholders.